Keanekaragaman Jenis Kantong Semar (Nepenthes spp.) di Kawasan Pelestarian Plasma Nutfah (KPPN) PT. Mua ra Sungai Landak Kabupaten Mempawah - Masnur Turnip, Waironius Jeffri, Rafdinal (Jurnal Protobiont, 2017)
Germplasm conservation area (GCA) refers to an area managed by PT. Muara Sungai Landak. This area is a peat swamp forest and a former location of deforestation. In addition, it has a wide variety of plants, for example Nepenthes. This research aims to determine the types and diversity of Nepenthes in the germplasm conservation area (GCA) of PT. Muara Sungai Landak, in Siantan sub district, Mempawah region, West Kalimantan. The research was conducted since September to December 2016. The research site was determined based on its environment colour. Data in this research was collected through systematic sampling technique. The findings showed that there were 3 types of Nepenthes in the germplasm conservation area, i.e. Nepenthes ampullaria, Nepenthes bicalcarata and Nepenthes rafflesiana. The diversity of Nepenthes spp. in this area was considered low. Dominance index shows that C (0,9363 - 0,9642) < 1, diversity index shows that H’ (0,3767 - 0,6467) < 1, and evenness index shows that E (0,5435 – 0,5886) < 1.